How attractive is Shariah Index Fund? - Mohd Yusop, Mohd Mahyudi; Omar, Mohd. Azmi (IIUM Institute of Islamic Banking and Finance, 2009)
Hakim and Rashidian (2002) observe that there is an increasing interest in socially responsible investments and index funds worldwide. Based on this point, a shari'ah index found seems to posses huge potentials for it carries the appeal of being both, a socially responsible investment and index fund. In the Malaysian context, high savings rate and low units trust contribute to the success of a shari'ah index fund. This study aims to analyze and evaluate the performance aspects of the Kuala Lumpur Shariah Index (KLSI) as compared to KLCI and RHB Islamic Index (RHBII) since April 1999 until June 2005, in order to complement the promising outlook of a shari'ah index fund. The method employed involves the measurement of performance; and measurement of risk, selectivity and timing. It also attempts to discover the characteristics of beta for Islamic stocks in Malaysia, as estimated via the market model using the ordinary least squares and generalized method of moments techniques. The findings show that the Islamic betas are positive and less than one. More importantly, the results reveal that the KLSI is of poorer quality than RHBII and the KLSI is of not market competitive. Thus, we conclude by propping the introduction of the Islamic version of the KLCI.